Drumbeat in our feet - Keeler, Patricia A. (Lee & Low Books, 2006)
"Informative passages and lyrical verse explore the history and rhythmic qualities of traditional African dance as performed long ago and today. Note about Harlem-based African dance troupe Batoto Yetu, photographs, and map in backmatter"--Provided by publisher.